IMPROVING MECHANISMS FOR ATTRACTING INVESTMENTS IN HIGHER EDUCATION IN UZBEKISTAN (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
This article provides opportunities for financing higher education through non-state investments and a mechanism for attracting higher educational institutions in Uzbekistan through the creation of endowment funds.